(untitled) (The Pakistan Development Review, 1997)
It is an honour for me as President of the Pakistan Society of Development Economists to welcome you to the 13th Annual General Meeting and Conference of the Society. I consider it a great privilege to do so as this Meeting coincides with the Golden Jubilee celebrations of the state of Pakistan, a state which emerged on the map of the postwar world as a result of the Muslim freedom movement in the Indian Subcontinent. Fifty years to the date, we have been jubilant about it, and both as citizens of Pakistan and professionals in the social sciences we have also been thoughtful about it. We are trying to see what development has meant in Pakistan in the past half century. As there are so many dimensions that the subject has now come to have since its rather simplistic beginnings, we thought the Golden Jubilee of Pakistan to be an appropriate occasion for such stock-taking.